Pattern of strengthening Islamic values in Islamic religious education learning at SMP Islam Terpadu Indah Medan - Azmi Siahaan; Indra Prasetia; Ellisa Fitri Tanjung (Indonesian Journal Education, 2026)
This study aims to analyze the pattern of strengthening Islamic values in Islamic Religious Education (PAI) learning at SMP Islam Terpadu Indah Medan through the integration of co-curricular and extracurricular activities. The research employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, and document analysis involving the vice principal, PAI teachers, and students. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure validity and credibility. The findings reveal that the reinforcement pattern is constructed through several interconnected strategies: religious habituation, vertical and horizontal integration of learning activities, social control and peer monitoring, the transformation of sanctions into spiritual development processes, differentiated coaching, and reward systems. These integrated patterns contribute to improving students’ discipline, responsibility, and the internalization of Islamic values in daily school life. The study offers a practical model for strengthening character-based Islamic education in school contexts.